Changes in Liver and Kidney Antioxidant Enzyme Activities in the Rainbow Trout (Oncorhynchus mykiss) Exposed Cadmium - HISAR, OLCAY; YILDIRIM, SUKRU; YAVUZ SONMEZ, ADEM; NUR ARAS, HATICE; GULTEPE, NEJDET (Asian Journal of Chemistry, 2010)
In vivo effects of cadmium on antioxidant enzymes such as superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx) and glutathione reductase (GSR) investigated in liver and kidney tissues of rainbow trout (Oncorhynchus mykiss). Three test groups of fish were subjected to cadmium in concentrations of 0 (control), 1 and 5 ppm. The duration of exposure was 1, 3, 5 and 7 d. The antioxidant enzyme activities, measured liver and kidney homogenates, were stimulated by both concentration (1 and 5 ppm) of cadmium chloride. Moreover, the dose-response patterns of the antioxidant enzyme activities in the liver and kidney tissue were very similar. All antioxidant enzyme activities were significantly stimulated on the first day of experiment (Day 1) in the tissues at the both dose of Cd (p < 0.05) while CAT activity was stimulated after 3 days in the tissues at a dose of 1 ppm Cd (p < 0.05). The stimulation effect of Cd on SOD, GPx and GSR activities in the tissues diminished after 7 d cadmium administration. However, this effect of Cd on CAT activity diminished after 5 d. These findings indicate that the tissue antioxidant enzymes function to protect against cadmium toxicity.